2016
DOI: 10.1007/s10549-016-4053-z
|View full text |Cite
|
Sign up to set email alerts
|

Previous GWAS hits in relation to young-onset breast cancer

Abstract: Purpose Genome-wide association studies (GWAS) have identified dozens of single nucleotide polymorphisms (SNPs) associated with breast cancer. Few studies focused on young-onset breast cancer, which exhibits etiologic and tumor-type differences from older-onset disease. Possible confounding by prenatal effects of the maternal genome has also not been considered. Methods Using a family-based design for breast cancer before age 50, we assessed the relationship between breast cancer and 77 GWAS-identified breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 79 publications
0
24
0
Order By: Relevance
“…Dysregulation of the expression of lincRNAs may be pervasive in human cancers and drives cancer development and progression [35]. Previous researches demonstrated that there are SNPs on LINC01376 associated with breast cancer [36,37]. Notably, it was the only lncRNA upregulated in our analysis with a logFC of 5.88, and it scored the best AUC (0.913) among all candidates.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Dysregulation of the expression of lincRNAs may be pervasive in human cancers and drives cancer development and progression [35]. Previous researches demonstrated that there are SNPs on LINC01376 associated with breast cancer [36,37]. Notably, it was the only lncRNA upregulated in our analysis with a logFC of 5.88, and it scored the best AUC (0.913) among all candidates.…”
Section: Resultsmentioning
confidence: 73%
“…Another lncRNA-AS that stood out in our analysis was ZNF667-AS1, with a logFC of approximately − 5.16 and an AUC of 0.717. Other studies have demonstrated that ZNF667-AS1 is commonly downregulated in several cancer types, including UCEC [36,37]. Vrba and colleagues [45] showed that it is expressed in all normal finite lifespan human cells examined to date and is downregulated or lost in immortalized human mammary epithelial cells.…”
Section: Resultsmentioning
confidence: 98%
“…With complete trios, previously reported statistics 8 become equivalent to statistics from the transmission-disequilibrium test and correlation among them is expected to follow the LD among SNPs. 8 We selected four candidate genes (TOX3, ESR1, FGFR2 and RAD51B ), for which Min et al 26,27 replicated several previously reported risk SNPs in relation to breast cancer.…”
Section: Combining Breast Cancer Association Statistics Within Candidmentioning
confidence: 89%
“…We applied our decorrelation method to a family-based GWAS study of breast cancer. 26,27 The data set was comprised of complete trios, i.e., families where genotypes of both parents and the affected offspring were available. With complete trios, previously reported statistics 8 become equivalent to statistics from the transmission-disequilibrium test and correlation among them is expected to follow the LD among SNPs.…”
Section: Combining Breast Cancer Association Statistics Within Candidmentioning
confidence: 99%
“…(Figure 1 of Weinberg et al 18 ). In this paper we assess interactions between the same 77-SNP PRS 3 and 14 established risk factors for breast cancer using data from a family-based genome-wide association study (GWAS) of young-onset (under age 50) breast cancer, the Two Sister Study.…”
mentioning
confidence: 99%